Samoświadomość a typ religijności - badania empiryczne adolescentów - Śliwak, Jacek; Szołdra, Marek (Space – Society – Economy, 2005)
Self-awareness is an immanent factor of modern human behaviour. It shows its presence in various situations of everyday life, during interpersonal contacts, in decisions making, conflicts, or attribution and making judgments (compare Zaborowski 2000, p. 7). This omnipresence of selfawareness in human life, encourages research on this subject. On the other hand, religiousness – which touches the idea of humanity itself, has many important functions in personality structure and in social functioning of an individual or a group. Religiousness becomes one of the basic determinants of correct development. To define the criteria of mature religiousness becomes a necessary condition. Religiousness becomes more significant in the context of youth, because this social group seems to be contesting, also holding in contempt social or moral norms, and as a consequence, also religious rules. Therefore, we can say that self-awareness and religiousness, are the one of basic levels of human existing. Taking everything above into consideration, the subject of connection between self-awareness and religiousness in adolescents was researched. The aim was to find connections between different types of self - awareness (examined using the Oleszkiewicz and Zaborowski self-awareness scale) and types of religiousness, understood as the experience of relations with God (examined using the Dirk Hutseband Questionnaire of Religiousness Relations).